Kekuatan Lentur dan Kekuatan Impak Komposit Matrik Epoxy Berpenguat Serat Sisal (Agave Sisalana) Menggunakan Metode Vacuum Bagging - Asrian, Angga; Putri Nawangsari; Fatra, Warman; Masnur, Dedy (SURYA TEKNIKA, 2025)
Agave Sisalana is widely grown in the Bukit Bulek area, West Sumatra Province. The Sisal leaf fiber is traditionally utilized by the Bukit Bulek community as a rope material. This indicates it has a great potential to be developed as a composite reinforcement material. This research aims to characterize the flexural and impact strength of Sisal leaf fiber as reinforcement in epoxy matrix composites by varying the fiber volume fractions, 30%, 35%, 40%, and 45% with a 0°/90° fiber orientation laminate. The 20 cm long of fibers and treated with 5% NaOH alkaline solution for 4 hours were employed. The composites were fabricated using the vacuum bagging method. Flexural and impact tests were conducted based on ASTM D-790 and ASTM D-6110 standards, respectively. The results show that the flexural strength increases from 45,20 to 49,67 MPa (maximum) as the fiber volume fraction increases from 30% to 35% fiber. Meanwhile, the impact strength increases as fiber volume fractions from 30% to 45% and reaches a maximum impact strength of 24.60 kJ/m².